Implementation of Islamic Education Principles in The Modern Madrasa Curriculum: A Study of Ta'lim Al-Muta'allim - Suherman Suherman; Abdul Ghofur; Raharjo Raharjo; Muhamad Priyatna; Isrofil Mirajul Arsyadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study examines the implementation of Islamic education principles from the book Ta'lim al-Muta'allim by Burhanuddin al-Zarnuji in the learning process at madrasas. These principles emphasize the importance of adab (etiquette), sincere intentions, and ethics in education, which remain relevant to modern educational contexts. Method: Using a qualitative approach with a case study methodology and literature review, this research combines in-depth interviews, observations, and document analysis to explore how these principles are applied in Madrasah Al Ishlah. Results: The findings reveal that key principles such as right intention, respect for teachers, diligence, and knowledge practice have been successfully integrated into the learning environment at Madrasah Al Ishlah. These principles have significantly contributed to developing students' character, including discipline, responsibility, and noble morals. However, challenges persist in balancing moral education with the academic demands of the curriculum. Novelty: This study highlights the relevance of Ta'lim al-Muta'allim in contemporary Islamic education, demonstrating that its principles not only enhance the quality of religious education but also offer a robust model for character education in madrasas, bridging the gap between academic achievements and moral development.